PENGARUH FOTOPERIOD TERHADAP KEPADATAN Sceletonema costatum SKALA LABORATORIUM - Nurfalaa, Nurfalaa; Rosyida, Eka; Ya'la, Zakirah Raihani (FAPETKAN UNTAD, 2016)
Sceletonema costatum is one of a live feed with a golden brown box shape with a relatively small size about 4-15 microns, and has a high nutrient content. The research objective was to study the effect of long exposure (photoperiod) to the density of Sceletonema costatum in laboratory scale. The research was conducted in October to November 2015, taking place at the Laboratory of Aquaculture, Faculty of Animal Husbandry and Fisheries, University Tadulako, Palu. The study used completely randomized design consisting of 4 treatments, (A) 12 light : 12 dark, (B) 14 light : 10 dark, (C) 16 light : 8 black, and (D) 18 light : 6 dark. The results showed the higher density of Sceletonema costatum cells are in treatment(C) 16 light : 8 dark as counted of 6.7 x 105 cells / ml.Keywords : Sceletonema costatum, Photoperiode, Density